2009
DOI: 10.1007/s11701-009-0123-0
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal robotic renal surgery: technique and early results

Abstract: We describe a robotic retroperitoneal approach to renal surgery, optimized in porcine and cadaveric models, and applied to human patients. A retroperitoneal approach for robotic kidney surgery was developed in nonsurvival porcine and a fresh cadaver models, and then utilized in ten patients (three partial nephrectomy, three radical nephrectomy, two simple nephrectomy, one pyeloplasty, one cryoablation). Retroperitoneal access was successfully achieved for robotic renal procedures in six pigs and a human cadave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Consequently, the results may not be applicable to the urologic community at large. Our study focused on a transperitoneal approach for RPN, although we did include a subset analysis of patients who underwent a retroperitoneal RPN and we have previously described our experience with a retroperitoneal approach for robotic kidney surgery [37]. Patients who underwent a retroperitoneal approach had similar perioperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the results may not be applicable to the urologic community at large. Our study focused on a transperitoneal approach for RPN, although we did include a subset analysis of patients who underwent a retroperitoneal RPN and we have previously described our experience with a retroperitoneal approach for robotic kidney surgery [37]. Patients who underwent a retroperitoneal approach had similar perioperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al [4] reported a series of 10 patients who underwent robotic retroperitoneal renal surgery (three partial nephrectomies, three radical nephrectomies, two simple nephrectomies, one pyeloplasty and one cryoablation). Patel et al [4] reported a series of 10 patients who underwent robotic retroperitoneal renal surgery (three partial nephrectomies, three radical nephrectomies, two simple nephrectomies, one pyeloplasty and one cryoablation).…”
Section: Discussionmentioning
confidence: 99%
“…We use the transperitoneal route, as do most of the RPN series reported. A retroperitoneal approach has also been described [19] .…”
Section: Methodsmentioning
confidence: 99%